Sex and Age-Based Differences in Immune Responses to a Peptide Vaccine for Melanoma in Two Clinical Trials - Serena M. Vilasi; Craig L. Slingluff (Vaccines)
Objectives: Little is known about the impact of patient age and biological sex on immune responses to melanoma vaccines, especially CD4+ T cell immune responses to peptides presented by Class II MHC molecules. Methods: We assessed the impact of age and sex on CD4+ T cell and antibody responses to a mixture of six melanoma helper peptides (6MHP) and on CD8+ T cell responses when vaccinating with 12 class I MHC-restricted melanoma peptides (12MP) plus either 6MHP or a tetanus helper T cell peptide (Tet). We hypothesized that immune responses would be greater in men and in younger patients. Results: We found differences in immune response by sex, but they favored female patients and were only evident for helper T cell responses to Tet with a weak trend to higher T cell responses to 12MP in female patients vaccinated with 12MP + Tet. The age-based differences favored younger patients but only for immune response to 12MP when inoculated with 12MP + Tet. Conclusions: These findings reinforce the importance of assessing sex- and age-based differences in immune responses to cancer vaccines and other immune therapies. There is also a need to understand the reasons for such differences.